Preparation, characterization and evaluation of aspirin: benzoic acid cocrystals with enhanced pharmaceutical properties - Braham Dutt; Manjusha Choudhary; Vikas Budhwar (SpringerOpen, 2020)
Abstract Background The cocrystallization process in pharmaceuticals has gained widespread attention as a recent method of modifying physicochemical properties without altering the pharmacological characteristics of drugs. Cocrystallization provides a couple of benefits like it can be employed for a large number of APIs (acidic, basic, ionizable, or non-ionizable), and secondly, the availability of a large number of potential coformers increases the possibility of the cocrystals (CCs) that can be synthesized for an API. The main objective of this study was to investigate the effects of cocrystallization on drugs having poor aqueous solubility. Results Aspirin (AN) and benzoic acid (BZ) were cocrystallized by using the solvent evaporation technique. CSD (Cambridge Structure Database) software and ∆pKa value method were used for the selection of the drug and coformer and for prediction of CC formation. The analysis of CCs was performed using DSC (differential scanning calorimetry), FT-IR (Fourier transformation infra-red spectroscopy) and XRD (X-ray diffraction) techniques. In vivo anti-inflammatory studies were conducted on 24 Wistar rats divided into four groups. Conclusions Here, in this study, in vitro dissolution studies revealed an improved solubility profile of CCs compared to pure drug and marketed formulation viz. 87%, 31% and 60% respectively. The in vivo anti-inflammatory studies exhibited improved anti-inflammatory activity compared to pure drug. So, on the basis of outcomes of this study, we concluded that cocrystallization process have a direct impact on the improvement of physicochemical characteristics of APIs having issues like solubility or stability without any modification and alteration of their pharmacological actions.